Placebo Manipulations Reverse Pain Potentiation by Unpleasant Affective Stimuli - Reicherts, Philipp; Pauli, Paul; Mösler, Camilla; Wieser, Matthias J. (Frontiers in Psychiatry, 2019)
According to the motivational priming hypothesis, unpleasant stimuli activate the motivational defense system, which in turn promotes congruent affective states such as negative emotions and pain. The question arises to what degree this bottom-up impact of emotions on pain is susceptible to a manipulation of top-down driven expectations. To this end, we investigated whether verbal instructions implying pain potentiation vs. reduction (placebo or nocebo expectations) - later on confirmed by corresponding experiences (placebo or nocebo conditioning) - might alter behavioral and neurophysiological correlates of pain modulation by unpleasant pictures. We compared two groups, which underwent three experimental phases: first participants were either instructed that watching unpleasant affective pictures would increase pain (nocebo group), or that watching unpleasant pictures would decrease pain (placebo group) relative to neutral pictures. During the following placebo/nocebo conditioning phase, pictures were presented together with electrical pain stimuli of different intensities, reinforcing the instructions. In the subsequent test phase, all pictures were presented again combined with identical pain stimuli. EEG was recorded in order to analyze neurophysiological responses of pain (somatosensory evoked potential, SEP) and picture processing (visually evoked late positive potential, LPP), in addition to pain ratings. In the test phase, ratings of pain stimuli administered while watching unpleasant relative to neutral pictures were significantly enhanced in the nocebo group, thus confirming the motivational priming effect for pain perception. In the placebo group, this effect was reversed such that unpleasant compared to neutral pictures led to significantly lower pain ratings. Similarly, SEPs were decreased during unpleasant compared to neutral pictures, in the nocebo group only. LPPs of the placebo group failed to discriminate between unpleasant and neutral pictures, while the LPPs of the nocebo group showed a clear differentiation. We conclude that the placebo manipulation already affected the processing of the emotional stimuli and in consequence the processing of the pain stimuli. In summary, the study revealed that the modulation of pain by emotions, albeit a reliable and well-established finding, is further tuned by reinforced expectations - known to induce placebo/nocebo effects -, which should be addressed in future research and considered in clinical applications.